Leisure‐time physical activity and sarcopenia among older adults from low‐ and middle‐income countries. Issue 2 (5th March 2023) - Jacob, Louis; Gyasi, Razak M.; Oh, Hans; Smith, Lee; Kostev, Karel; López Sánchez, Guillermo F.; Rahmati, Masoud; Haro, Josep Maria; Tully, Mark A.; Shin, Jae Il; Yon, Dong Keon; Koyanagi, Ai
Abstract: Background: There are no data on the association between leisure‐time physical activity (LTPA) and sarcopenia in older adults from low‐ and middle‐income countries (LMICs). This study aimed to investigate the association between LTPA and sarcopenia in individuals aged ≥65 years living in six LMICs. Methods: Cross‐sectional data from the Study on Global AGEing and Adult Health (China, Ghana, India, Mexico, Russia and South Africa) were analysed. Sarcopenia referred to the presence of both low skeletal muscle mass and weak handgrip strength. LTPA was assessed using the Global Physical Activity Questionnaire and was analysed as a dichotomized variable [high LTPA (>150 min/week of moderate‐to‐vigorous LTPA) or low LTPA (≤150 min/week)]. Multivariable logistic regression analysis was conducted to assess associations. Results: There were 14 585 individuals included in this study [mean (SD) age 72.6 (11.5) years; 55.0% women]. The prevalence of high LTPA and sarcopenia was 8.9% and 12.0%, respectively. After adjusting for potential confounders, low LTPA was significantly associated with higher odds for sarcopenia [prevalence odds ratio (POR) = 1.85, 95% confidence interval (CI) = 1.29–2.65] compared with high LTPA. Significant associations were found in women (POR = 3.22, 95% CI = 1.82–5.68) but not in men (POR = 1.52, 95% CI = 0.99–2.35). Conclusions: A positive and significant association between low LTPA and sarcopenia was found among older adults from LMICs. The promotion of LTPA among older adults in LMICs may aid in the prevention of sarcopenia, especially among females, pending future longitudinal research.